UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE - Sumar Sumar (JURNAL GLOBAL EDUKASI, 2019)
Abstract: This study aims to determine the ability of Mathematics learning outcomes material to determine the elements, parts of the circle and its size by using a think pair share learning model in class VIII-3 students of SMP Negeri 1 Meranti in the academic year 2017/2018. The location of this research is in SMP Negeri 1 Meranti, Asahan district. The study was conducted in semester II of the 2017/2018 school year. The measure by looking at the hypothesis and the initial test performance indicator is 57.14% of the total number of 20 students who have shown the ability to category is not good. After class action research the average value in the first cycle was 76.65, students who finished learning 74.28%. In the second cycle, it is included in the good category, namely students have reached an average of 84.2, completeness learning is 85% at the end of cycle II. Keywords: think pair share, circle  Abstrak: Penelitian ini bertujuan untuk mengetahui kemampuan hasil belajar Matematika  materi menentukan unsur, bagian lingkaran serta ukurannya dengan menggunakan model pembelajaran think pair share pada siswa kelas VIII-3 SMP Negeri 1 Meranti tahun pelajaran 2017/2018. Lokasi penelitian ini  adalah di SMP Negeri 1 Meranti, kabupaten Asahan. Penelitian dilaksanakan pada semester II tahun pelajaran 2017/2018. Ukurannya dengan melihat hipotesis dan indikator kinerja test awal adalah 57.14% dari keseluruhan jumlah 20 siswa yang sudah menunjukan kemampuan hingga kategori kurang baik. Setelah penelitian tindakan kelas nilai rata-rata pada siklus I adalah 76.65, siswa yang tuntas belajar 74.28%. Pada siklus II sudah termasuk pada kategori baik yaitu siswa telah mencapai rata-rata 84,2, ketuntasan belajar yaitu 85% akhir siklus II. Kata kunci: think pair share, lingkaran